Irf3 polymorphism alters induction of interferon beta in response to Listeria monocytogenes infection. - Oleg Garifulin; Zanmei Qi; Haihong Shen; Sujatha Patnala; Michael R Green; Victor Boyartchuk (PLoS Genetics, 2007)
Genetic makeup of the host plays a significant role in the course and outcome of infection. Inbred strains of mice display a wide range of sensitivities to Listeria monocytogenes infection and thus serve as a good model for analysis of the effect of genetic polymorphism. The outcome of L. monocytogenes infection in mice is influenced by the ability of this bacterium to induce expression of interferon beta mRNA, encoded in mouse by the Ifnb1 (interferon beta 1, fibroblast) gene. Mouse strains that lack components of the IFN beta signaling pathway are substantially more resistant to infection. We found that macrophages from the ByJ substrain of the common C57BL/6 inbred strain of mice are impaired in their ability to induce Ifnb1 expression in response to bacterial and viral infections. We mapped the locus that controls differential expression of Ifnb1 to a region on Chromosome 7 that includes interferon regulatory factor 3 (Irf3), which encodes a transcription factor responsible for early induction of Ifnb1 expression. In C57BL/6ByJ mice, Irf3 mRNA was inefficiently spliced, with a significant proportion of the transcripts retaining intron 5. Analysis of the Irf3 locus identified a single base-pair polymorphism and revealed that intron 5 of Irf3 is spliced by the atypical U12-type spliceosome. We found that the polymorphism disrupts a U12-type branchpoint and has a profound effect on the efficiency of splicing of Irf3. We demonstrate that a naturally occurring change in the splicing control element has a dramatic effect on the resistance to L. monocytogenes infection. Thus, the C57BL/6ByJ mouse strain serves as an example of how a mammalian host can counter bacterial virulence strategies by introducing subtle alteration of noncoding sequences.